The association between maternal social support levels during pregnancy and child development at three years of age: the Japan Environment and Children's Study - Yousuke Imanishi; Satoyo Ikehara; Yuri Aochi; Tomotaka Sobue; Hiroyasu Iso; The Japan Environment and Children's Study Group (Komiyama Printing Co. Ltd, 2024)
Background: Social relationships are essential in maintaining the physical and mental health of mothers and their children. However, there is limited evidence on how social support provided to the mother during pregnancy could impact child development. Herein, we examined whether maternal social support levels during pregnancy was associated with the risk of developmental delay in 3-year-old children. Methods: Overall, 68,442 mother-child pairs completed questionnaires on maternal social support during pregnancy and development delay in 3-year-old children. The maternal social support level was evaluated using four items. The risk of development delay was evaluated using the Japanese version of the Ages and Stages Questionnaire-3 (ASQ-3) with five domains of communication, gross motor, fine motor, problem-solving, and personal-social. Odds ratios (OR) and 95% confidence intervals (CI) were calculated using logistic regression according to the quintiles of maternal social support levels after adjusting for potential confounding factors. Results: Social support during pregnancy was associated with a lower risk of development delay at 3 years of age. Beneficial effects were detected in all domains of the ASQ-3 (p for trend <0.001). Multivariable ORs (95% CIs) for the highest versus lowest quartiles of maternal social support level were 0.57 (0.50-0.65) for communication, 0.49 (0.43-0.55) for gross motor delay, 0.58 (0.53-0.64) for fine motor delay, 0.56 (0.51-0.62) for problem-solving delay, and 0.52 (0.45-0.60) for personal social delay. The associations remained unchanged when stratified by maternal education level, paternal education level, living with children, household income, and postpartum depression. Conclusion: Maternal social support during pregnancy was inversely associated with the risk of developmental delay at 3 years of age.